Real Tropical Hyperfaces by Patchworking in polymake - Joswig, Michael (Mathematical Software – ICMS 2020, 2020)
An implementation of Viro’s patchworking in polymake is presented, and a census of Betti numbers of real tropical surfaces serves as a showcase. The latter is relevant in the context of Hilbert’s 16th Problem.